PERANCANGAN APLIKASI PENCATATAN KAS DONASI PADA YAYASAN BINA YATAMA - Muhamad Ilham; Arie Ardiansyah (Shofanah Media Berkah, 2023)
The Bina Yatama Foundation is an institution or organization engaged in the socio-religious field. With the increasing amount of data stored, it has made it difficult for the Foundation to manage all the data received, resulting in a buildup of files. From these problems it is encouraging to design a system by utilizing computer technology, especially in the use of the internet which is processed with an accurate management information system, the design of this system aims to help improve services at the Bina Yatama Foundation in managing donor data and related processes and reports systematically. Therefore the design of this system is made on a web basis to make it easier for the Foundation to manage the data needed. In this web application we use the UML (Unified Modeling Language) modeling language. In addition, the tools used in designing this system are using the PHP programming language and MySQL database for data storage. The results of this research, in the form of a web-based donor management fund management information system, are expected to help the performance of the Bina Yatama Foundation in improving its services to donors and providing accurate information to be given to donors in need.